IMPLEMENTASI AKAD IJARAH DALAM PEMBIYAAN PENDIDIKAN DI LEMBAGA KEUANGN MIKRO SYARIAH (STUDI KASUS : BMT AL-ITTIFAQIAH) - Ratna; Alif Dzulkarnaini; hidayani; hairunnisa (LA RIBA: Jurnal Perbankan Syariah, 2024)
This research aims to find out how customers respond to the use of ijarah financing at BMT Al-Ittifaqiah, customers in using ijarah financing at BMT Al-Ittifaqiah, and to find out what factors influence customer satisfaction and interest in using ijarah financing at BMT al-Ittifaqiah . The method used is a qualitative research method, the type of research used in this research is field research which is descriptive qualitative in nature, the data analysis used is using an inductive thinking method. The results of this research show that customer responses at BMT Al-Ittifaqiah are very useful and provide satisfaction for customers or student guardians. And there are two factors that influence customer satisfaction in using ijarah financing at BMT Al-Ittifaqiah, namely internal factors (personality), motivation, attitudes and beliefs, lifestyle and religion) and external factors (service, promotion and location). The conclusion of this research is that the experience or satisfaction felt by customers at BMT Al-Ittifaqiah is in accordance with the customer's wishes or interests in terms of using ijarah financing, especially education, and customers at BMT Al-Ittifaqiah are interested in using ijarah financing specifically for educational factors.